Acute Stress Affects the Expression of Hippocampal Mu Oscillations in an Age-Dependent Manner - Takillah, Samir; Naudé, Jérémie; Didienne, Steve; Sebban, Claude; Decros, Brigitte; Schenker, Esther; Spedding, Michael; Mourot, Alexandre; Mariani, Jean; Faure, Philippe (Frontiers in Aging Neuroscience, 2017)
Anxiolytic drugs are widely used in the elderly, a population particularly sensitive to stress. Stress, ageing and anxiolytics all affect low-frequency oscillations in the hippocampus and prefrontal cortex independently, but the interactions between these factors remain unclear. Here, we compared the effects of stress (elevated platform) and anxiolytics (diazepam) on extracellular field potentials in the prefrontal cortex, parietal cortex and hippocampus (dorsal and ventral parts) of adult (8 months) and aged (18 months) Wistar rats. A potential source of confusion in the experimental studies in rodents comes from locomotion-related theta (6-12 Hz) oscillations, which may overshadow the direct effects of anxiety on low-frequency and especially on the high-amplitude oscillations in the Mu range (7-12Hz), related to arousal. Animals were restrained to avoid any confound and isolate the direct effects of stress from theta oscillations related to stress-induced locomotion. We identified transient, high-amplitude oscillations in the 7-12Hz range (“Mu-bursts”) in the prefrontal cortex, parietal cortex and only in the dorsal part of hippocampus. At rest, aged rats displayed more Mu-bursts than adults. Stress acted differently on Mu-bursts depending on age: it increases vs. decreases burst, in adult and aged animals, respectively. In contrast Diazepam (1mg/kg) acted the same way in stressed adult and age animal: it decreased the occurrence of Mu-bursts, as well as their co-occurrence. This is consistent with diazepam acting as a positive allosteric modulator of GABAA receptors, which globally potentiates inhibition and has anxiolytic effects. Overall, the effect of benzodiazepines on stressed animals was to restore Mu burst activity in adults but to strongly diminish them in aged rats. This work suggests Mu-bursts as a neural marker to study the impact of stress and diazepam on age.